Light-absorbing capacity of volcanic dust from Iceland and Chile - Koivusalo, Taru F. A.; Dagsson-Waldhauserová, Pavla; Gritsevich, Maria; Peltoniemi, Jouni (Frontiers in Earth Science, 2024)
It is increasingly recognized that light-absorbing impurities (LAI) deposited on snow and ice affect their albedo and facilitate melting processes leading to various feedback loops, such as the ice albedo feedback mechanism. Black carbon (BC) is often considered the most important LAI, but some areas can be more impacted by high dust emissions. Iceland is one of the most important high latitude sources for the Arctic due to high emissions and the volcanic nature of the dust. We studied optical properties of volcanic dust from Iceland and Chile to understand how it interacts with the Sun's radiation and affects areas of deposition as LAI. Optical properties of dust samples were measured at the laboratory of the Finnish Geospatial Research Institute (FGI) using the latest setup of the FGI's goniospectrometer. We found that, depending on the particle size, the albedo of dry volcanic dust on the visible spectrum is as low as 0.03, similar to that of BC, and the albedo decreases with increasing particle size. Wet dust reduces its albedo by 66 % compared to dry sample. This supports the comparability of their albedo reducing effects to BC as LAIs, and highlights their significant role in albedo reduction of snow and ice areas. The potential use of the results from our measurements is diverse, including their use as a ground truth reference for Earth Observation and remote sensing studies, estimating climate change over time, as well as measuring other ecological effects caused by changes in atmospheric composition or land cover.